BiovaxID, a personalized therapeutic vaccine against B-cell lymphomas - Reiniš, Milan (Current opinion in molecular therapeutics, 2008)
Biovest International Inc (a subsidiary of Accentia BioPharmaceuticals Inc), under license from Stanford University, is developing BiovaxID, a personalized therapeutic vaccine against B-cell lymphomas that, in combination with GM-CSF, exclusively targets cancerous B-cells by raising an immune response to tumor-specific immunoglobulin proteins called idiotypes, for the potential treatment of follicular non-Hodgkin's lymphoma (NHL). Phase I and II clinical trials demonstrated the immunogenicity, safety and therapeutic efficacy of BiovaxID. Phase III clinical trials in NHL were ongoing at the time of publication.
Keywords: Granulocyte-Macrophage Colony-Stimulating Factor; Cancer Vaccines; Humans; Mice; zvířata; B-buněčný lymfom; folikulární lymfom; Clinical Trials, Phase I as Topic; Clinical Trials, Phase II as Topic; protinádorové vakcíny; Lymphoma, B-Cell; klinické zkoušky, fáze I jako téma; myši; Lymphoma, Follicular; faktor stimulující granulocyto-makrofágové kolonie; Animals; lidé; Vaccination; klinické zkoušky, fáze II jako téma; vakcinace